Preparing for Disasters: Your food and drinking water supply - Amy H. Simonne (EDIS)
Having enough clean drinking water is a top priority during any emergency! A normally active person needs at least two quarts of water each day. However, needs vary depending on the weather and an individual’s age and health status. When clean water is not available, we need to purify all water before using it for drinking, preparing food, or personal hygiene. Many methods for purifying water are available, but none (by itself) is perfect. Often, a combination of more than one methods works best. This document is FCS9195, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: May 2003.